MobEx model : its effect on ankle dorsiflexion range of motion, dynamic balance and ankle functional ability measures in athletes with and without previous history of lateral ankle sprain - Mohansundar Sankaravel (2021)
Lateral Ankle Sprains (LAS) are the most common soft tissue injuries among athletes. This study aimed to examine the effects of a six-week MobEx Model Intervention Program on athletes without previous history of Lateral Ankle Sprains (W/OLAS) and athletes with a previous history of Lateral Ankle Sprains (WLAS), specifically to alter the intrinsic risk factors consist of ankle dorsiflexion range of motion, dynamic balance, functional ability of the ankle. A single blinded prospective randomized control trail with experimental cross-sectional research design was used in this study. The researcher recruited 33 athletes W/OLAS and 27 athletes WLAS independently. They were randomized into MobEx Group (MGR N=20), Placebo Group (PCR N=20) and Control Group (CGR N=20). The MGR undergone six weeks MobEx Model Intervention Program, the PGR received placebo intervention for six weeks and the CGR received no intervention. Baseline measurements were taken for DF ROM by Weight Bearing Lunge Test, dynamic balance by Modified Bass Test for Dynamic Balance, and foot and ankle ability measure for Activities of Daily Living (FAAMADL) and Sports Subscale (FAAM-SS) using Foot and Ankle Ability Measure questionnaire before and after the intervention. After one month, these variables were measured again for retention test. The MANOVA test results revealed that there are significant differences among all criterion measures at <0.05 for athletes W/OLAS and athlete WLAS. Study findings indicated that MobEx Model Intervention Program revealed significant effects on intrinsic risk factors i.e. DF ROM and dynamic balance at = 0.000, respectively. Thereby, improving, and enduring FAAM-ADL and FAAMSS at = 0.000 respectively for athletes W/OLAS and athlete WLAS. This study is suggesting that the intervention program is effective and clinically significance to alter intrinsic risk factors for lateral ankle sprains among athletes.